1992
DOI: 10.1093/jnci/84.23.1825
|View full text |Cite
|
Sign up to set email alerts
|

Can Thymidine Kinase Levels in Breast Tumors Predict Disease Recurrence?

Abstract: Higher TK1 levels in tumors in patients who subsequently had disease recurrence almost certainly indicate a high rate of proliferation in such tumors at the time of excision. It appears that TK is a potentially useful marker in the management of breast cancer. With measurement of levels of TK, particularly TK1, in breast tumors and serum, it may be possible to predict recurrence of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…14,30 The kit used here for TK measurement is optimized for the fetal cytosolic TK1 isoenzyme. In experimental models, TK1 expression also has been strongly associated with S-phase: 31 TK1 increases markedly after the G1-S transition 8,12 and a high affinity TK1 tetramer is specifically found in S-phase cells. 32,33 Although TS activity has been associated with proliferation, it has not been closely linked with S-phase.…”
Section: Multivariate Prognostic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…14,30 The kit used here for TK measurement is optimized for the fetal cytosolic TK1 isoenzyme. In experimental models, TK1 expression also has been strongly associated with S-phase: 31 TK1 increases markedly after the G1-S transition 8,12 and a high affinity TK1 tetramer is specifically found in S-phase cells. 32,33 Although TS activity has been associated with proliferation, it has not been closely linked with S-phase.…”
Section: Multivariate Prognostic Analysesmentioning
confidence: 99%
“…8,12 High TK values have been correlated with poor survival, 8,[13][14][15][16] especially in node-negative patients receiving no systemic adjuvant therapy. 13,16 However, the relative importance of TK and other quantitative measures of proliferation is currently unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Its activity fluctuates with DNA synthesis, being high in dividing and malignant cells and low in quiescent cells. 6,7 TK2 is considered to be located in the mitochondria; levels of TK2 remain relatively constant throughout the cell cycle. Clinical studies have reported elevated serum TK activity in various human malignancies.…”
mentioning
confidence: 99%
“…8 The majority of these studies concerned hematologic malignancies, but serum TK activity was also elevated in patients with epithelial ovarian cancer. 9 Additionally, serum and cytosolic TK activities appear to have prognostic value in some solid tumors, such as breast, 7,10,11 small cell lung, 12 prostate 13 and cervical 14 cancers. However, little is known about the clinical and prognostic value of tissue TK gene expression in human cancers.…”
mentioning
confidence: 99%